Full-endoscopic uniportal retropharyngeal odontoidectomy: A preliminary case report - Ye, Jichao; Liu, Bin; Li, Jinteng; Zheng, Guan; Duan, Kaidi; Gao, Liangbin; Zhang, Chunyan; Huang, Jingwen; Tang, Yong (Frontiers in Surgery, 2023)
Summary of Background Data: Odontoidectomy aims to decompress the medulla oblongata, and usually be performed through the classical transoral approach which affects oropharynx and accompanied with high rate of complications comprising swallowing and respiratory tract. We have developed a minimal invasive method via a standard cervical anterior approach: full-endoscopic trans-cervical odontoidectomy, which provides an alterative access for the resection of odontoid process and medulla oblongata decompression without traversing potentially contaminated cavities. Methods：From 2018 to 2020, three patients with either odontoid process lesion or basilar invagination underwent full-endoscopic uniportal trans-cervical odontoidectomy with/without combining the posterior instrumentation. With fluoroscopic guidance, a uniportal endoscope sleeve was placed inside of the odontoid process, then odontoid process was gradually resected from the inside to outside under endoscopic monitoring. Postoperative images and clinical data were collected during post-op follow up. Result: Patients were soon extubated after surgery when patients wake up from general anesthesia. There were no severely perioperative complications, especially dysphagia and airway obstruction, and the symptoms and neurological function was improved immediately after surgery. The final pathology of one patient with odontoid osteolytic lesion was confirmed as plasmacytoma. The postoperative CT scans proved that the range of odontoid process resection was consistent with the preoperative expectation. Conclusion: In summary, our proposed endoscopic trans-cervical odontoidectomy provides a valid choice for non-oral approach, which would reduce postoperative approach related complications and accelerate postoperative recovery.